Fabrication of micro solid oxide fuel cell by thin film processing hybridization: I. Multilayer structure of sputtered YSZ thin film electrolyte and Ni-based anodes deposited by spray pyrolysis - Son, J.-W.; Kim, H.; Kim, H.-R.; Lee, J.-H.; Lee, H.-W.; Bieberle-H？tter, A.; Rupp, J.L.M.; M？ecke, U.P.; Beckel, D.; Gauckler, L.J. (Korean Ceramic Society, 2007)
Physical properties of sputtered YSZ thin film electrolytes on anode thin film by spray pyrolisis has been investigated to realize the porous electrode and dense electrolyte multilayer structure for micro solid oxide fuel cells. It is shown that for better crystallinity and density, YSZ need to be deposited at an elevated temperature. However, if pure NiO anode was used for high temperature deposition, massive defects such as spalling and delamination were induced due to high thermal expansion mismatch. By changing anode to NiO-CGO composite, defects were significantly reduced even at high deposition temperature. Further research on realization of full cells by processing hybridization and cell performance characterization will be performed in near future.